Targeting a cysteine protease from a pathobiont alleviates experimental arthritis - Hsin-Yi Peng; Shih-Yao Chen; Shih-Hong Siao; Jinghua Tsai Chang; Ting-Yin Xue; Yi-Hsuan Lee; Ming-Shiou Jan; Gregory J. Tsay; Moncef Zouali (Arthritis Research & Therapy, 2020)
Abstract Background Several lines of evidence suggest that the pathobiont Porphyromonas gingivalis is involved in the development and/or progression of auto-inflammatory diseases. This bacterium produces cysteine proteases, such as gingipain RgpA, endowed with the potential to induce significant bone loss in model systems and in patients. Objective We sought to gain further insight into the role of this pathobiont in rheumatoid arthritis (RA) and to identify novel therapeutic targets for auto-inflammatory diseases. Methods We profiled the antibody response to RgPA-specific domains in patient sera. We also tested the potential protective effects of RgpA domains in an experimental arthritis model. Results Pre-immunization of rats with purified recombinant RgpA domains alleviated arthritis in the joints of the rodents and reduced bone erosion. Using a functional genomics approach at both the mRNA and protein levels, we report that the pre-immunizations reduced arthritis severity by impacting a matrix metalloprotease characteristic of articular injury, a chemokine known to be involved in recruiting inflammatory cells, and three inflammatory cytokines. Finally, we identified an amino acid motif in the RgpA catalytic domain of P. gingivalis that shares sequence homology with type II collagen. Conclusion We conclude that pre-immunization against gingipain domains can reduce the severity of experimentally induced arthritis. We suggest that targeting gingipain domains by pre-immunization, or, possibly, by small-molecule inhibitors, could reduce the potential of P. gingivalis to translocate to remote tissues and instigate and/or exacerbate pathology in RA, but also in other chronic inflammatory diseases.